Pharmacopeial Standards for the Quality Control of Botanical Dietary Supplements in the United States. (4th May 2023) - Sarma, Nandakumara; Upton, Roy; Rose, Ulrich; Guo, De-an; Marles, Robin; Khan, Ikhlas; Giancaspro, Gabriel
Abstract: Botanicals are among the fastest growing segments of the dietary supplement industry in the U.S. The Dietary Supplement Health and Education Act (DSHEA; Public Law 103-417 [Oct. 25, 1994]) provided a regulatory classification for the trade of numerous botanicals and botanically-derived products as dietary supplements. The global supply chain, the adoption of many botanicals that are also recognized as traditional medicines around the world as dietary supplement ingredients, and the differing recognition of the national and international pharmacopeias as sources for voluntary or mandatory quality standards present challenges in ensuring the quality of the ingredients and products. The complexity of quality assurance by compliance with pharmacopeial standards is illustrated in this article with a brief history of pharmacopoeias including their official recognition in national laws, their approaches to the science behind the standards, the use of reference standards for quality assessment and regulatory compliance, the use of pharmacopeial standards by the industry and regulators within the DSHEA framework in the United States, and a discussion of the global supply chain. Pharmacopeial standards can help regulators and the industry adapt to the new technologies that present both opportunities and challenges.